Class Wars: Initial Steps Into The Fray - Lebor, Merv (Teaching in Lifelong Learning: A Journal to Inform and Improve Practice, 2013)
This article explores the issue of preparing trainee teachers for the challenges of how to face their students’ ‘disruptive behaviour’ which sometimes marks the beginning and sets the tone for the remainder of sessions. In this paper I explore my work mentoring two trainee teachers, looking at the options available to them on entering classrooms where students displayed disruptive behaviour. There is a context of Ofsted criteria, whereby disruptive behaviour is no longer acceptable and ‘failure’ is allocated as an observation grade where ‘disruptive behaviour’ occurs. This piece offers an exploration of classroom management strategies for preparing trainee teachers who face challenging situations in Further Education (FE) environments and suggests strategies for dealing with the difficulties of disruptive classes. The reason why this is vitally important is because trainee teachers in Cert Ed classes wish to discuss this issue more than any other topic. It affects their self-esteem, confidence and class interaction in delivering the curriculum.